Protection of First Nations cultural heritage : laws, policy, and reform - Bell, Catherine E. (Catherine Edith), 1961-; Paterson, Robert K., 1946- (Law and society series (Vancouver, B.C.), 2009)
"This companion volume to First Nations Cultural Heritage and Law looks at the key features of Canadian, US, and international law influencing indigenous cultural heritage in Canada. Legal and extralegal avenues for reform are examined, including ethics codes, research protocols, institutional policies, human rights law, and First Nation legal orders. The book also discusses the opportunities and limits of existing frameworks and questions whether a radical shift in legal and political relations is necessary for First Nations concerns to be meaningfully addressed."--Jacket.